Biotechnological approaches to control the crop pathogen Fusarium and development of nanotechnology-based diagnostic methods for detection of plant diseases. - Botella, José Ramón (My University, 2014)
The plant fungal pathogen Fusarium is the causal agent of ‘Fusarium wilt’ and results in large losses on a wide range of crops including vegetables, flowers, trees and field crops. Control methods for Fusarium wilt are very limited. Crop rotations are ineffective because F. oxysporum has such a large host range and is able to survive in the soil for long periods of time and genetic resistance is very scarce or on-existent in many crops. I will describe the development of two biotechnological approaches to produce fusarium resistant plants, one of which has produced 100% resistance. I will also present the development of nanotechnology-based diagnostic methods that can be coupled with DNA electrode recognition technology to detect and identify over 100,000 different pathogens in a single diagnostic test.
Seminario de experto en el tema de Biotecnología de Plantas
Keywords: Biotecnología